Adverse Perinatal Events Associated with ART - Skora, Daniel; Frankfurter, David (Seminars in Reproductive Medicine, 2012)
Since the advent of ART, much research has focused on the potential adverse for resultant harm. Prematurity, low birth-weight, PIH, congenital malformations, and CP are closely tied to multiple gestation. With the increase in elective single embryo transfer, there will be a reduction in adversity related to multiple birth. It is understood that underlying causes of infertility, including advanced maternal age, PCOS, thyroid disease, and uterine fibroids, predispose to adverse outcomes. However, imprinting abnormalities do not appear to stem from multiple births, and thus the need to consider the association between fertility treatment and methylation disorders remains essential. These, as well as risks of multi-fetal gestation, must be discussed with patients when considering using assisted reproduction.
Keywords: assisted reproduction; multiple birth; methylation disorder; perinatal morbidity and mortality; cerebral palsy; congenital malformation